2017
DOI: 10.3847/1538-4357/aa9656
|View full text |Cite
|
Sign up to set email alerts
|

Ionized-gas Kinematics Along the Large-scale Radio Jets in Type-2 AGNs

Abstract: To investigate the connection between radio activity and AGN outflows, we present a study of ionized gas kinematics based on [O III] λ5007 emission line along the large-scale radio jet for six radio AGNs. These AGNs are selected based on the radio activity (i.e., L 1.4GHz 10 39.8 erg s −1 ) as well as optical emission line properties as type 2 AGNs. Using the Red Channel Cross Dispersed Echellette Spectrograph at the Multiple Mirror Telescope, we investigate in detail the [O III] and stellar kinematics. We spa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…This is supported by the 'FIRST Classifier' (Alhassan et al 2018), which automatically identifies FIRST sources as compact or not, and determines that all of our sources are compact except for J1430+1339. This cautions against only relying on low-resolution radio data to identify low power/compact radio structures not associated with star formation in such systems (e.g., see Kimball et al 2011;Le et al 2017).…”
Section: Properties Of the Observed Radio Emissionmentioning
confidence: 99%
“…This is supported by the 'FIRST Classifier' (Alhassan et al 2018), which automatically identifies FIRST sources as compact or not, and determines that all of our sources are compact except for J1430+1339. This cautions against only relying on low-resolution radio data to identify low power/compact radio structures not associated with star formation in such systems (e.g., see Kimball et al 2011;Le et al 2017).…”
Section: Properties Of the Observed Radio Emissionmentioning
confidence: 99%
“…σ [OIII,out] is often considered as a tracer of outflow signatures in AGNs (e.g., Greene & Ho 2005a;Bae & Woo 2014;Woo et al 2016;Le et al 2017). In our analysis, we determined the outflow strengths of our sample such as σ [OIII,out] and V max .…”
Section: Maximum Outflow Velocitymentioning
confidence: 99%
“…This angular size is well defined within the SDSS aperture size. Following their method, we estimated the NLR size for our local SDSS and high redshift samples by using the size-luminosity relation (e.g., Bae et al 2017;Le et al 2017). Based on the bolometric luminosity of our sample, we estimated the [O III] luminosity of our local SDSS and high redshift samples to be in the range of L OIII ∼ 10 41.5 -10 43 erg s −1 (L bol = 700 × L OIII , LaMassa et al 2009).…”
Section: Aperture and Rotational Broadening Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have revealed that the fraction of galaxies hosting AGNs is higher in GV galaxies, compared to red sequence (RS) and blue cloud (BC) galaxies (e.g., Silverman et al 2008;Schawinski et al 2010;Wang et al 2017). However, most of the evidence about the AGN activities interacting with the star formation within these galaxies is indirect (e.g., Silk & Rees 1998;Ishibashi & Fabian 2012;Zubovas et al 2013;Cresci et al 2015;Le et al 2017aLe et al , 2017bShin et al 2019). If AGN feedback indeed drives the quenching within these galaxies, then the timescales that the central black holes remain active should be comparable to the color transition timescales of GV galaxies.…”
Section: Introductionmentioning
confidence: 99%